From inquiry learning innovation: The impact of maggot BSF (Black Soldier Fly) on school organic waste mitigation and sustainability awareness - Pramita Sylvia Dewi; Alif Luthvi Azizah; Muhisom Muhisom; Dina Maulina; Rahmiati Darwis (Education and Development Research, 2026)
The purpose of this study is to develop a learning model that not only improves students' understanding of inquiry innovation on the concept of recycling and organic waste management but also builds environmental awareness and responsibility. This study uses a descriptive method with a quantitative approach. The research sample used purposive sampling; junior high school students at this school were selected because they have a vegetable garden, in accordance with the needs of the investigation activities. Data were collected through an inquiry sheet, then analyzed descriptively, and environmental actions were reviewed for gender differences through a questionnaire tested with MANOVA, with the results of Sig. 0.023 < 0.05 for student attitudes and Sig. 0.083 > 0.05 for knowledge, which means that only gender influences students' environmental actions. In the context of ESD, which demands social action and environmental responsibility, it turns out that female students can be more prominent in attitudes. This explains why gender can influence attitudes. Furthermore, this study is a reflection on the relationship between environmental awareness and real actions. The implications of research activities that involve students in observing, researching, and analyzing the life cycle of BSF maggots and their role in decomposing organic waste create a learning experience oriented towards sustainability awareness.